Peningkatan Hasil Belajar IPA Melalui Pembelajaran Kooperatif Tipe Jigsaw terhadap Siswa Kelas VI SD - St Syamsiah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This type of research is a classroom action research (Classroom Action Research) which aims to determine the improvement of biology science learning outcomes through jigsaw type cooperative learning for class VI students of SD Inpres 10/73 Maroanging, Bone Regency, on the concept of the human circulatory system. The subjects of this study were Grade VI students of SD Inpres 10/73 Maroanging, Bone Regency in 2022. This research was conducted in 2 cycles. Before the first cycle was carried out, preliminary observations were carried out. Each cycle consists of: action planning, action implementation, observation and evaluation, and reflection. The mplementation of the second cycle is an improvement from the implementation of the first cycle. Data on learning outcomes were analyzed quantitatively, while the results of observations of student activities were analyzed qualitatively. The results showed that the average value of material mastery or student learning outcomes in the first cycle was 5.53 and in the second cycle was 7.55. The results of the observation of student activities also increased. The results of the analysis can be concluded that the application of jigsaw cooperative learning can improve students' science learning outcomes.